Cytokine competent gut-joint migratory T Cells contribute to inflammation in the joint - Lefferts, Adam R.; Norman, Eric; Claypool, David J.; Kantheti, Uma; Kuhn, Kristine A. (Frontiers in Immunology, 2022)
Although studies have identified the presence of gut-associated cells in the enthesis of joints affected by spondylarthritis (SpA), a direct link through cellular transit between the gut and joint has yet to be formally demonstrated. Using KikGR transgenic mice to label in situ and track cellular trafficking from the distal colon to the joint under inflammatory conditions of both the gut and joint, we demonstrate bona-fide gut-joint trafficking of T cells from the colon epithelium, also called intraepithelial lymphocytes (IELs), to distal sites including joint enthesis, the pathogenic site of SpA. Similar to patients with SpA, colon IELs from the TNFdARE/+ mouse model of inflammatory bowel disease and SpA display heightened TNF production upon stimulation. Using ex vivo stimulation of photo-labeled gut-joint trafficked T cells from the popliteal lymph nodes of KikGR and KikGR TNFdARE/+ we saw that the CD4+ photo-labeled population was highly enriched for IL-17 competence in healthy as well as arthritic mice, however in the TNFdARE/+ mice these cells were additionally enriched for TNF. Using transfer of magnetically isolated IELs from TNF+/+ and TNFARE/+ donors into Rag1-/- hosts, we confirmed that IELs can exacerbate inflammatory processes in the joint. Finally, we blocked IEL recruitment to the colon epithelium using broad spectrum antibiotics in TNFdARE/+ mice. Antibiotic-treated mice had reduced gut-joint IEL migration, contained fewer Il-17A and TNF competent CD4+ T cells, and lessened joint pathology compared to untreated littermate controls. Together these results demonstrate that pro-inflammatory colon-derived IELs can exacerbate inflammatory responses in the joint through systemic trafficking, and that interference with this process through gut-targeted approaches has therapeutic potential in SpA.